UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENT) - Ristika Ristika (Prodi Pendidikan Matematika, STKIP PGRI Bandar Lampung, 2022)
The problem behind this research is the low learning outcomes of students in mathematics in class V SD IT Khairul Ummah Bandar Lampung and the lack of activeness of students in the learning process. These problems arise due to several factors, including learning that has not fully activated students. In connection with the above problems, this study aims to improve the mathematics learning outcomes of fifth grade students by applying the TGT (Teams Games Tournament) learning model. This research is a collaborative Classroom Action Research (CAR). This Classroom Action Research consists of four stages, namely: planning, implementation, observation and reflection. This research was conducted at SD IT Khairul Ummah Bandar Lampung with the research subject being class V with a total of 35 students. The results showed that the application of the TGT (Teams Games Tournament) type of cooperative learning model could improve students' mathematics learning outcomes. This is indicated by the increase in the percentage of student learning completeness, namely at the time of pre-action by 31%, increasing to 57% in the first cycle, then increasing again in the second cycle to 80%. This result exceeds the established research success indicator, which is 75%. In addition, from the observation data obtained before the action was given, the students looked less active in learning activities and learning activities were not yet centered on students. After being given the action, the students looked active both during question and answer activities and during group activities. Thus, in each cycle there is an increase and it can be concluded that the TGT (Teams Games Tournament) type cooperative learning model can improve the learning outcomes of fifth grade students at SD IT Khairul Ummah Bandar Lampung for the 2021/2022 school year.